Bioactivity of Kipahit Flower Extract Tithonia Diversifolia on Mortality and Eating Behavior of Larvae Crocidolomia Pavonana - Pertiwi, Fitri Dewi; Syahputra, Edy; Ramadhan, Tris Haris (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2024)
Using of synthetic insecticides to control the C. pavonana pest could have negative impacts. As an alternative control, using plant extracts is relatively safer in controlling these pests. This research aims to study the bioactivity flower of kipahit T. diversifolia extract on mortality and feeding behavior of C. pavonana larvae. Extraction was carried out using the maceration method using methanol. Bioassay for insecticidal activity was carried out using the residual method on the leaves against larvae II. Feeding on treated leaves was carried out for 48 hours. the antifeedant assayed for 24 hours of exposure to instar III. The concentration - mortality relationship was analyzed using probit analysis. Data on development time are expressed as the average value ± standard deviation. The results showed that the activity of kipahit flower extract had an LC50 of 0.51% and an LC95 of 3.86%. These extract with choicw method at the sub lethal dose tested inhibit the feeding activity by 24.90%, 53.96%, 76.34% respectively, while the no choice method inhibits feeding activity by 27.20%, 59.69% 86.40%, respectively.